2016
DOI: 10.1163/1568539x-00003373
|View full text |Cite
|
Sign up to set email alerts
|

Into the wild: developing field tests to examine the link between elasmobranch personality and laterality

Abstract: The field of animal personality has received considerable attention in past decades, yet few studies have examined personality in the wild. This study investigated docility, a measure of boldness, in two Port Jackson shark (Heterodontus portusjacksoni) populations using field tests, and if laterality differences explained docility levels. We developed a struggle test as an assay for docility, which is particularly amenable to field studies. The struggle test was effective, and repeatable inter-individual docil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…For 14 individuals that were captured and handled on two occasions, we assessed repeatability of struggling scores (and see Byrnes et al. , for a similar method for elasmobranchs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 14 individuals that were captured and handled on two occasions, we assessed repeatability of struggling scores (and see Byrnes et al. , for a similar method for elasmobranchs).…”
Section: Methodsmentioning
confidence: 99%
“…To date, few behavioral studies have demonstrated personality differences in the wild (but see Byrnes et al. , May et al. ); yet validating behavioral traits with ecological (and physiological) data is pivotal to understanding the evolution of personality variation in natural populations (Réale et al.…”
Section: Introductionmentioning
confidence: 99%
“…Repeatable individual behavioural traits such as boldness, activity, or sociability, for example, have now been widely demonstrated in teleosts (Budaev & Brown, 2011) and more recently in sharks (Byrnes et al, 2016b;Finger et al, 2017;Jacoby et al, 2014). Personality traits have been linked to the way individuals make decisions, which includes social behaviour decision-making (Raoult et al, 2017;Sih & Del Giudice, 2012;Trompf and Brown, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the behavioral attributes of wild reptiles, researchers must adapt their scoring systems to the ecology of the species in question (Byrnes et al., 2016; Ward‐Fear et al., 2018). The four behavioral measures listed below are appropriate for assaying lace monitors along a shyness/boldness axis (see Results).…”
Section: Methodsmentioning
confidence: 99%